Implementation of Independent Learning Curriculum Management in Improving the Character of Learners at PKBM Mekar Asri Margorejo Surabaya - Kartika, Amalia; Huriyah, Lilik (Universitas Ibn Khaldun, 2025)
This research was based the management of the independent learning curriculum at PKBM Mekar Asri which has the potential to improve the character of students. The aim of this research is to find out more broadly about the implementation of Merdeka Belajar curriculum management, in this case related to improving the character of students in PKBM. The research method used is qualitative research with data collection techniques through observation, interviews and documentation. Technical data analysis is carried out through data reduction, data presentation and drawing conclusions. The results of this research show that the implementation of the Independent Learning Curriculum improves the character of students at PPKBM Mekar Asri, namely through two activities, first, problem solving activities or the ability to solve problems by making the right decisions. Second, through P5 activities (Strengthening Pancasila Student Profile Project). Meanwhile, evaluation of the implementation of the Independent Learning Curriculum is carried out once a year, namely at the end of every even semester.